Pengaruh Budaya Organisasi, Gaya Kepemimpinan Dan Partisipasi Penganggaran Terhadap Kinerja Manajerial (Studi pada PT. Pos Indonesia Persero Metro) - Anam, Khoirul; Suwarto, Suwarto (Jurnal Manajemen DIVERSIFIKASI, 2023)
AbstractManagerial performance in an organization is very important, because good managerialperformance can create an organization's competitive advantage. There are many factorsthat can improve the quality of managerial performance including organizational culture,leadership style and budgeting participation. The purpose of this study was to analyze theinfluence of organizational culture, leadership style and budgeting participation onmanagerial performance at PT. Pos Indonesia Persero Metro. The method used in thisresearch is the explanatory survey method. The objects in this study are organizationalculture, leadership style, budgeting participation and managerial performance. This researchactivity was conducted at PT. Pos Indonesia Persero Metro. The research population isemployees of PT. Pos Indonesia Persero Metro with the number of samples taken as many as40 respondents. Data collection techniques using questionnaires. The results showed thatpartially organizational culture, leadership style and budgeting participation had a positiveand significant effect on managerial performance. Simultaneously organizational culture, leadership style and budgetary participation also have a significant influence on managerialperformance.Keywords: Organizational Culture, Leadership Style, Budgeting Participation, ManagerialPerformance